Drug interaction assessment following concomitant administration of posaconazole and phenytoin in healthy men - Krishna, Gopal; Sansone-Parsons, Angela; Kantesaria, Bhavna (Current medical research and opinion, 2007)
ABSTRACT Objective: Posaconazole is an extended-spectrum triazole antifungal agent for the treatment and prophylaxis of invasive fungal infections. This randomized, open-label, parallel-group, multiple-dose study was conducted in healthy adult volunteers to assess the potential for a drug interaction between phenytoin and the posaconazole tablet formulation. Methods: Subjects were randomly assigned for 10 days to one of the following treatments: posaconazole (200 mg once daily), phenytoin (200 mg once daily), or posaconazole (200 mg once daily) and phenytoin (200 mg once daily). Blood samples were collected on days 1 and 10 for pharmacokinetic evaluation of posaconazole and phenytoin concentrations. Results: A total of 36 healthy men enrolled in the study. On day 1, the maximum plasma concentration (Cmax) and area under the concentration–time curve calculated from time 0–24 h post-dose (AUC(0–24)) were unchanged upon co-administration. At steady state (day 10), co-administration of posaconazole with phenytoin resulted in 44% ( p = 0.012) and 52% ( p = 0.007) decreases in posaconazole Cmax and AUC(0–24), respectively. These decreases in exposure corresponded with a 90% increase in steady-state clearance of orally administered posaconazole. Phenytoin Cmax and AUC(0–24) were not significantly altered upon co-administration of the two agents, 24% increase in Cmax ( p = 0.196) and 25% increase in AUC(0–24) ( p = 0.212) values, although inter-subject variability was observed within this group. Conclusion: Because co-administration of phenytoin and posaconazole significantly reduces posaconazole exposure and increases phenytoin levels in some subjects, concomitant use of these agents should be avoided unless the benefit outweighs the risk.